BUDDHIST ETHICS PROMOTION FOR LOCAL ADMINISTRATIVE ORGANIZATION ADMINISTRATORS IN SURAT THANI PROVINCE - โสภา, สุภาภรณ์; หมั่นมี, ธิติวุฒิ; ดอกไธสง, บุญทัน (Journal of MCU Social Science Review, 2020)
Objectives his research were to: 1. Study the Buddhist ethics attributes for local administrative organization administrators in Surat Thani Province, 2. Study the factors related to the Buddhist ethics promotion for local administrative organization administrators in Surat Thani Province and 3. Propose a format of Buddhist ethics promotion for local administrative organization administrators in Surat Thani Province. Methodology was mixed methods. The quantitative research collected data by questionnaires with the validity score at 0.982 from 361 samples who were administrators, officers and employees by accidental sampling, analyzed data with frequency, percentile, mean, standard deviation and Pearson’s product-moment correlation coefficient. The qualitative research collected data from 25 key informants with structured in-depth-interview form by face-to-face interviewing and also from 10 participants in focus group discussion. Data from the two steps were analyzed by descriptive interpretation. Findings were as follows: 1. Attributes of Buddhist ethics for local administrative organization administrators in Surat Thani Provice, by overall, were at a high level (x=3.81). Each aspect of attributes: imitativeness, personality, aims, enthusiasm, friendliness, reliability, boldness in decision-making, proficiency, faithfulness and trustworthiness were all at high levels. 2. Factors related to Buddhist ethics promotion for local administrative organization administrators in Surat Thani Province were that Buddhist ethics attribute for local administrative organization administrators was positively correlated at a high level (r = 0.887) with a statistical significance level of 0.01, and the promotion of Buddhist ethics according to Ethical Tree theory was positively correlated at a high level (r=0.928) with a statistical significance level of 0.01accepting the hypothesis of the research. 3. The format Buddhist ethics promotion for local administrative organization administrators in Surat Thani Province comprises 10 aspects: the persistence of democratic form of government with the King as Head of State in accordance with Buddhist ethical principles; adherence to moral virtues in accordance with Buddhist ethical principles; possession of good conscience, honesty and responsibility in accordance with Buddhist ethical principles; holding benefit of the nation above personal benefit and avoiding conflicts of interest on a foundation of Buddhist ethics; the insistence on doing what is right, fair and lawful in accordance with Buddhist ethical principles; the provision of fast and friendly service to the public; the provision of complete and accurate information to the public, intention to achieve work results that maintains standards, possess transparent quality and can be verified in accordance with Buddhist ethical principles; adherence to the organization’s principles of professional conduct in accordance with Buddhist ethical principles; and building the awareness of the local population to act as good citizens in accordance with Buddhist ethical principles.